Quasi-radical operation on the submodules in a module - (:unkn) unknown (My University, 2011)
All rings are commutative with identity and all modules are unital. The purpose of this paper is to introduce interesting and useful properties of quasi-radical operation on the submodules in a module.© 2011 Academic Journals.
Keywords: Prime submodules; Qausi-radical operation